Teoria da regulação francesa e o Sistema Financeiro Nacional - Cascione, Fábio de Souza Aranha (2011)
The occurrence of the great crisis of 2008, comparable in structure to the crisis of 1929, he resurrected the relevance of the study of French regulation theory, largely forgotten in the 2000s (largely due to the prevalence of neoliberal thinking in OECD countries and in some emerging economies such as Brazil). This can be explained by the approach of the scholars of regulation theory about capitalism have begun the study of a crisis of capitalism. Specifically, the final crisis of Fordism in the 1970s, as discussed below. This paper will seek, through the French school of regulation - of Marxist origin - have a look at the Brazilian capitalist mode of regulation in a critical way, and illuminate new possibilities for state intervention in the economy (particularly in the National Financial System), conforms with the establishment of just social relations. The suggestion for a new form of intervention of the National Financial System state1 would be possible and even legitimate, after a good grasp of the theory of regulation.